An actor-network analysis of the healthcare worker influenza immunisation programme in Wales: 2009-2011 - Hale, Rachel (2016)
Frontline healthcare workers (HCWs) in the UK have been prioritised for free occupational immunisation against seasonal influenza since 1999. During the 2009-10 influenza pandemic, they were identified as a priority group to receive the strain-specific vaccine. Nevertheless, take-up rates among HCWs have rarely exceeded 50%, even during the pandemic. Most attempts to change this situation have been predicated on the assumption that these low rates are the result of reluctance or resistance by individual HCWs, who must be persuaded or coerced to comply with employer directives.